2021
DOI: 10.1038/s41598-021-81583-z
|View full text |Cite
|
Sign up to set email alerts
|

Foraging niche partitioning in sympatric seabird populations

Abstract: Sympatric species must sufficiently differentiate aspects of their ecological niche to alleviate complete interspecific competition and stably coexist within the same area. Seabirds provide a unique opportunity to understand patterns of niche segregation among coexisting species because they form large multi-species colonies of breeding aggregations with seemingly overlapping diets and foraging areas. Recent biologging tools have revealed that colonial seabirds can differentiate components of their foraging st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…For each bird, we calculated the time spent foraging in each visited 0.5 x 0.5° cell. To identify foraging/resting state (hereafter foraging, see Fromant et For SGDP, the speed threshold was 9.1 km•h -1 , with a drift speed of 5 km•h -1 (Petalas et al 2021), and average flight speed of 50 km•h -1 . Average flight speed was estimated from the analysis of 15 flying bouts (with regular fixes) using raw data.…”
Section: Track Analysismentioning
confidence: 99%
“…For each bird, we calculated the time spent foraging in each visited 0.5 x 0.5° cell. To identify foraging/resting state (hereafter foraging, see Fromant et For SGDP, the speed threshold was 9.1 km•h -1 , with a drift speed of 5 km•h -1 (Petalas et al 2021), and average flight speed of 50 km•h -1 . Average flight speed was estimated from the analysis of 15 flying bouts (with regular fixes) using raw data.…”
Section: Track Analysismentioning
confidence: 99%
“…Within our study area, we documented considerable intraspecific variability in foraging ranges and distance from coastlines. Foraging effort and ranges may also be influenced by interspecific competition within colonies (Delord et al, 2020;Petalas et al, 2021) as well as density-dependent intraspecific competition and interference driven by colony size (Lewis et al, 2001;Grecian et al, 2012;Gaston et al, 2013;Jovani et al, 2016) and local prey abundance and/or prey condition (Burke and Montevecchi, 2009;Elliott et al, 2009). We were unable to formally test this with our data given the small number of tracked colonies for each species (in contrast to Wakefield et al, 2017).…”
Section: Foraging Rangesmentioning
confidence: 85%
“…Several studies have shown that trophically similar species switch to using different foraging substrates, as well as different attack manoeuvres to avoid competition and allowing coexistence (Kent & Sherry, 2020; Pigot et al, 2020). This is the case of species living in highly competitive environments as, for instance, large colonies of seabirds, where slight differences in foraging niches represent an evolutionary adaptation to reduce niche overlap (Petalas et al, 2021). Our findings show no association between co-migration fidelity and foraging strategies, neither in females, nor in males, possibly suggesting the onset of sex-independent foraging mechanisms promoting coexistence at stopover area.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all species investigated in our study have a strictly carnivorous diet and feed mainly on insects, with the exception of the European turtle dove, Streptopelia turtur and the Eurasian golden oriole Oriolus oriolus , which are classified mainly as granivores’ ground feeding species, but have nevertheless variable foraging niches [53]. Several studies have shown that species with similar diets switch to alternative foraging substrates and different predatory behaviour to avoid competition [53,71]. Our findings show no association between co-migration fidelity and foraging strategies, suggesting the existence of species-independent foraging mechanisms promoting coexistence at stopover areas.…”
Section: Discussionmentioning
confidence: 99%